2020
DOI: 10.1111/evj.13372
|View full text |Cite
|
Sign up to set email alerts
|

Implantable loop recorders can detect paroxysmal atrial fibrillation in Standardbred racehorses with intermittent poor performance

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Over the last couple of years, the horse has gained increasing interest as a large animal model of arrhythmias [18] , [19] , [20] , [21] , [22] . In contrast to other animal models usually used in AF research, such as rodents, pigs, dogs and goats, horses are frequently reported to develop AF spontaneously, just like humans [23] , [24] , [25] , [26] . Furthermore, spontaneous pulmonary vein firings were recorded in a horse recently, indicating that AF triggering processes might resemble the ones in humans, which supports the horse as a highly suitable and interesting animal for AF research [27] .…”
Section: Introductionmentioning
confidence: 94%
“…Over the last couple of years, the horse has gained increasing interest as a large animal model of arrhythmias [18] , [19] , [20] , [21] , [22] . In contrast to other animal models usually used in AF research, such as rodents, pigs, dogs and goats, horses are frequently reported to develop AF spontaneously, just like humans [23] , [24] , [25] , [26] . Furthermore, spontaneous pulmonary vein firings were recorded in a horse recently, indicating that AF triggering processes might resemble the ones in humans, which supports the horse as a highly suitable and interesting animal for AF research [27] .…”
Section: Introductionmentioning
confidence: 94%
“…Some studies report AF with no other diagnosed cardiac diseases, whereas others report one third of the horses with mild or moderate mitral regurgitation (Decloedt et al, 2015). Paroxysmal AF is believed to frequently occur in horses and may be responsible for periodic poor performance in racehorses (Buhl, Nissen, et al, 2020). In athletic horses, AF results in significant reduced physical performance, increased maximum heart rate (HR) and ventricular arrhythmias during high‐speed exercise treadmill tests (Buhl et al, 2018).…”
Section: Spontaneous Af In Large Animalsmentioning
confidence: 99%
“…Furthermore, we can improve our models by using animals known to develop spontaneous AF. In horses, for instance, it is possible to implant loop recorders to detect spontaneous episodes of AF (Buhl, Hesselkilde, et al, 2020; Buhl, Nissen, et al, 2020). This, combined with the fact that it is possible to take transvenous atrial biopsies in horses (Decloedt et al, 2016; Hesselkilde et al, 2020) will hopefully in the future give us the opportunity to study these episodes when they occur and elucidate structural myocardial changes, thereby providing more insight into the true aetiology of AF.…”
Section: Large Animal Models Of Afmentioning
confidence: 99%
“…It is the most common form of AF developing in association with racing and the majority of cases resolve without treatment in the 48 hours after onset 8 . New diagnostic tools such as smartphone‐based contactless ECG, 85–88 machine learning analysis of ECG records 64,65 and implantable loop recorders 89,90 may improve our understanding of the evolution of AF through remodelling.…”
Section: Arrhythmogenic Mechanisms Leading To Afmentioning
confidence: 99%